Gratitude – invisibly webbing society together. (February 2013) - Cantó-Milà, Natàlia
This paper traces a line between Simmel's formal sociology, his little-reviewed concept of 'forms of second order', his apriorities for social life and his incipient sociology of emotions. Thus different elements of Simmel's sociology are brought together and linked. These elements were all present in his 1908 monograph, Sociology, but were not connected to each other in the way that they have been interconnected here. The social form of 'gratitude' is presented as a paradigmatic 'form of second order', and thus illustrates the way in which forms of sociation, especially second-order forms of sociation, are deeply connected to the apriorities of social life.